The Punishment of Taking Life in Islamic and Jewish Law: A Comparative Study - علي محمد كريم محمد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study addresses the crime of taking a life, which ranks among the gravest offenses threatening both the individual and society. It constitutes a severe violation of the right to life, a fundamental right universally regarded by all divine laws as sacred and inviolable. Consequently, both Islamic and Judaic legal systems have devoted significant attention to this issue by establishing a rigorous legislative framework to define the various forms of homicide and prescribe appropriate rulings and penalties according to the degree of intent and the nature of the act. This research aims to clarify the similarities and differences between the Islamic and Judaic approaches to the crime of homicide, whether in terms of classification—namely intentional murder, quasi-intentional killing, and accidental killing—or regarding the determination of the penalties associated with each category. This analysis clearly reflects the higher objectives of the legislation in safeguarding the sanctity of life, preserving social order, and achieving justice understood within both religious and ethical dimensions. Furthermore, the study seeks to extract the jurisprudential and interpretative foundations of the punishments related to taking life in both Islamic and Talmudic teachings, through the analysis of scriptural texts from the Qur’an and the Torah, as well as the examination of the opinions of prominent jurists within both traditions, with particular emphasis on the Imami jurisprudence in Islam. Through this, the study endeavors to provide a profound insight into the punitive methodologies employed and their alignment with the principles of justice, mercy, and fairness in both religious philosophies